1914: Austria-Hungary, the Origins, and the First Year of World War I - Bischof, Günter (Contemporary Austrian Studies, 2014)
For the past 100 years some of the greatest historians and political scientists of the twentieth century have picked apart, analyzed and reinterpreted this sequence of events taking place within a single month in July/early August 1914. The four years of fighting during World War I destroyed the international system put into place at the Congress of Vienna in 1814/15 and led to the dissolution of some of the great old empires of Europe (Austrian-Hungarian, Ottoman, Russian). The 100th anniversary of the assassination of the Austrian successor to the throne Archduke Francis Ferdinand and his wife Sophie in Sarajevo unleashed the series of events that unleashed World War I. The assassination in Sarajevo, the spark that set asunder the European powder keg, has been the focus of a veritable blizzard of commemorations, scholarly conferences and a new avalanche of publications dealing with this signal historical event that changed the world. Contemporary Austrian Studies would not miss the opportunity to make its contribution to these scholarly discourses by focusing on reassessing the Dual Monarchy's crucial role in the outbreak and the first year of the war, the military experience in the trenches, and the chaos on the homefront.